Narcolepsy during Childhood: An Update - Rocca, Francesca Letizia; Pizza, Fabio; Ricci, Emilia; Plazzi, Giuseppe (Neuropediatrics, 2015)
Narcolepsy type 1 (NT1) is a rare central disorder of hypersomnolence characterized by excessive daytime sleepiness, cataplexy, sleep paralysis, hallucinations, and fragmented nocturnal sleep usually arising in adolescence or young adulthood. Recently, the childhood NT1 diagnoses have increased for improved disease awareness and for several cases occurring after the H1N1 pandemic influenza or vaccination. As in adults, the occurrence of NT1 in individuals with a genetic predisposition of the immune system (e.g., human leukocyte antigen, HLA-DQB1*0602) together with the role of environmental triggers (e.g., H1N1 influenza virus, streptococcus β hemolyticus) further supports the autoimmune pathogenesis. Children with NT1 close to disease onset show a peculiar cataplexy phenotype characterized by persistent hypotonia with prominent facial involvement (cataplectic facies) and by a complex mosaic of hyperkinetic movement abnormalities that increase during emotional stimulation. This phenotype progressively vanishes along the disease course leading to the typical picture of cataplexy (i.e., muscle weakness exclusively evoked by strong emotions). This possibly explains in part the misdiagnoses and diagnostic delay. Childhood NT1 also shows behavioral abnormalities and psychiatric disorders, encompassing depressive feelings, hyperactive/aggressive behavior, up to psychotic features. The association with obesity and precocious puberty strikingly suggests that NT1 arising in prepubertal children may reflect a wide hypothalamic derangement secondary to hypocretin neuronal loss. The complexity of the childhood NT1 phenotype claims a multidisciplinary assessment and management, taking behavioral and endocrinological features into account. NT1 indeed is a lifelong disorder with a devastating impact on quality of life, especially when arising across developmental age, and targeted school programs, medicolegal and psychological supports are essential for patients care. Controlled studies are mandatory to assess safety and efficacy of the current symptomatic off-label medications on which also relies the treatment for children with NT1, and hopefully future pathogenetic evidences will pave the way to better disease prevention and therapies to modify the disease course.
Keywords: cataplexy; precocious puberty; obesity; hallucinations; hyperactivity; psychiatry; movement disorders; polysomnography